Awareness and knowledge of female genital schistosomiasis in a population with high endemicity: a cross-sectional study in Madagascar - Rausche, Pia; Rakotoarivelo, Rivo Andry; Rakotozandrindrainy, Raphael; Rakotomalala, Rivo Solotiana; Ratefiarisoa, Sonya; Rasamoelina, Tahinamandranto; Kutz, Jean-Marc; Jaeger, Anna; Hoeppner, Yannick; Lorenz, Eva; May, Jürgen; Puradiredja, Dewi Ismajani; et al. (Frontiers in Microbiology, 2023)
Female genital schistosomiasis (FGS) is a neglected disease with long-term physical and psychosocial consequences, affecting approximately 50 million women worldwide and generally representing an unmet medical need on a global scale. FGS is the chronic manifestation of a persistent infection with S. haematobium. FGS services are not routinely offered in endemic settings with a small percentage of women at risk receiving adequate care. Madagascar has over 60 % prevalence of FGS and no guidelines for the management of the disease. This study aimed to determine FGS knowledge among women and health care workers (HCWs) in a highly endemic area of Madagascar.A convenience sampling strategy was used for this cross-sectional study. Descriptive statistics including proportions and 95% confidence intervals (CI) were calculated, reporting socio-demographic characteristics of the population. Knowledge sources were evaluated descriptively. Binary Poisson regression with robust standard errors was performed; crude (CPR) and adjusted prevalence ratio (APR) with 95% CIs were calculated.A total of 783 participants were included in the study. Among women, 11.3% (n=78) were aware of FGS while among the HCWs 53.8% (n=50) were aware of FGS.The highest level of knowledge was observed among women in an urban setting (24%, [ n=31]) and among those with a university education/vocational training (23% [n=13]). A lower APR of FGS knowledge was observed in peri-urban (APR 0.25 [95% CI: 0.15; 0.45]) and rural (APR 0.37 [95% CI 0.22; 0.63]) settings in comparison to the urban setting. Most HCWs reported other HCWs (40% [n=20]) while women mainly reported their family (32% [n=25]) as being their main source of information in the six months prior to the survey.Our study shows limited awareness and knowledge of FGS among population groups in the highly endemic Boeny region of Madagascar. With this study we contribute to identifying an important health gap in Madagascar, which relates to a disease that can silently affect millions of women worldwide. In alignment with the targets of the NTD roadmap, addressing schistosomiasis requires a paradigm shift for its control and management including a greater focus on chronic forms of the disease.